2012
DOI: 10.1007/s10461-012-0188-z
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive, Psychosocial, and Sociodemographic Predictors of Willingness to Use HIV Pre-Exposure Prophylaxis Among Chinese Men Who Have Sex with Men

Abstract: This study was designed to identify predictors of lower versus higher willingness to use pre-exposure prophylaxis (PrEP) to reduce HIV among men who have sex with men (MSM) in China. Participants were 570 MSM who completed self-report measures of willingness to use HIV PrEP, beliefs about HIV, psychosocial factors, sexual experiences and sociodemographic characteristics. Results of a hierarchical binary logistic regression analysis indicated that membership in a higher willingness group was predicted by previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
42
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 29 publications
9
42
0
Order By: Relevance
“…The willingness of PrEP use of MSM in Taiwan is consistent with 50-75% of willingness in the Asia-Pacific region and a U.S. context (Holt, 2014;Young & McDaid, 2014) and relative lower than 63-67.8% of Chinese MSM (Jackson et al, 2012;Zhou et al, 2012) and 88.4% of Thai MSM (Wheelock et al, 2013). The discrepancy between initial willingness and willingness to self-pay for PrEP is a consequence of PrEP cost and affordability.…”
Section: Discussionmentioning
confidence: 52%
“…The willingness of PrEP use of MSM in Taiwan is consistent with 50-75% of willingness in the Asia-Pacific region and a U.S. context (Holt, 2014;Young & McDaid, 2014) and relative lower than 63-67.8% of Chinese MSM (Jackson et al, 2012;Zhou et al, 2012) and 88.4% of Thai MSM (Wheelock et al, 2013). The discrepancy between initial willingness and willingness to self-pay for PrEP is a consequence of PrEP cost and affordability.…”
Section: Discussionmentioning
confidence: 52%
“…Five studies sampled participants from service provision sites such as community-based and youth-led non-governmental organizations [31,32,50,52]. Two studies utilized health facilities for recruitment and data collection, including community health clinics [53] and HIV voluntary counselling and testing sites [51]. Three studies utilized other venues frequented by MSM such as entertainment venues [33,47], gay community events [53], and beauty salons [50].…”
Section: Recruitment and Data Collection Settingsmentioning
confidence: 99%
“…The studies by Lim et al [31], Bourne et al [32], and Jackson et al [53] expanded their online-based recruitment to include recruitment through local non-governmental organizations, which may have facilitated inclusion of different profiles of MSM. A number of studies recruited specifically from sites which were thought to be frequented by high-risk MSM, including from entertainment venues in Thailand [33,47], gay community events in China [53], and beauty salons in Peru [50]. Although appropriate for identifying MSM who require PrEP, these strategies may exclude other MSM, for example those who are not living openly as MSM.…”
Section: Bias Assessmentmentioning
confidence: 99%
“…There has been growth in recent research examining attitudes, awareness and willingness to use PrEP among MSM primarily in the US, [7], [8], [9], [10], [11], [12] with more limited research in Australia, China, France, Thailand and Canada [13], [14], [15], [16], [17]. To date, only one peer-reviewed study with MSM in the UK has been published, [18] although preliminary findings from a few UK studies have been reported [19], [20].…”
Section: Introductionmentioning
confidence: 99%